A Novel Direct Weighted Deviation (DWD) Method for Agricultural Enterprise Selection: A Case Study of Namakkal District, Tamil Nadu - V. Sathiya; S. Mahalakshmi; S. Ramabalan; N. Godwin Raja Ebenezer (International Journal of Industrial and Product Design Engineering, 2026)
The study proposes a novel Direct Weighted Deviation (DWD) method for Multi-Criteria Decision Making (MCDM) by eliminating normalization, distance metrics, and pairwise comparisons. DWD is thereafter used to evaluate and select ten rainfed agricultural enterprises against ten generic and context-specific viability criteria in Namakkal District, Tamil Nadu, a water-scarce region in India. Subsequently, other methods (AHP, SAW, WPM, and TOPSIS) are used to obtain a comparative second opinion and validate the outcomes of the proposed method. Against the backdrop of timely reinforced sustainability and scalability considerations, DWD identifies Goat Rearing Enterprise as the top alternative, in close competition with Mango Cultivation and Dairy. The hybrid AHP-TOPSIS method, due to bias introduced by an unusually high subjective income-dependent criterion weight computed using AHP, erroneously ranks Layer Poultry first. A subsequent sensitivity analysis quantified the levels of bias, robustness, and stability of the three methods discussed. Sensitivity analysis of the alternatives and criteria was also performed. The results suggested that the DWD method is on par with the AHP-TOPSIS method but scores over the other two in all counts. Most significant advantage of DWD over the AHP-TOPSIS method is seen in its outperformance of the layer poultry enterprise in terms of livelihood security and water conservation potential, which are pertinent objectives in any semi-arid agricultural system.
Keywords: Novel MCDM method; Sensitivity analysis; Sustainable agriculture; Tamil Nadu; direct weighted deviation; multi-criteria decision making; water-scarce agriculture